Tata Kelola Badan Usaha Milik Desa “Wijaya” Desa Bejijong Kecamatan Trowulan Kabupaten Mojokerto - Dhohan, Ajie; Nawangsari, Ertien Rining (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The development of the potential of the village-owned business sector is currently a special attraction in Indonesia. One of them is the governance process carried out by the Village-Owned Enterprise "Wijaya" in Bejijong Village, Trowulan District, Mojokerto Regency. Evidenced by the fact that all activities from the initial process to management are carried out by BUMDesa Wijaya, so that many achievements have been made at the district, provincial and national levels thanks to the potential and good management of the village-owned business sector and being able to significantly increase PADes. This study aims to describe and analyze the governance of the “Wijaya” Village Owned Enterprise in Bejijong Village, Trowulan District, Mojokerto Regency. The research method used is descriptive qualitative. Data obtained through observation, interviews and documentation. From the research results obtained, it shows that the governance process carried out by BUMDesa "Wijaya" in developing the village-owned business sector is going well and is optimal in achieving its goals, because during the governance process, namely (1) there is cooperation with various stakeholders or stakeholders including BPCB East Java, The Lumbini Buddha Parini Bana Foundation and Mister Aladin; (2) the participation of various parties including the Bejijong Village Government, Ladewi Gajah Mada and the Bejijong Village community; (3) the provision of equal services to the people of Bejijong Village regardless of class, ethnicity and religion; (4) there is a transparent attitude towards the Bejijong Village community regarding the activities and information carried out; (5) there is accountability for their performance to Pemdes Bejijong in order to overcome conflicts of interest; (6) the involvement of the Pemdes Bejijong, Ladewi Gajah Mada and the Bejijong Village community.